Decreased IL-4 is the risk factor of depression in patients with Takayasu arteritis - Zhang, Yaxin; Yang, Shiyu; Fan, Anyuyang; Du, Juan; Gao, Na; Pan, Lili; Li, Taotao (Frontiers in Medicine, 2024)
Objective Depression is a common complication in Takayasu arteritis (TA). Disorders of the immune system play an important role in both diseases. This study aimed to clarify the feature of cytokines in TA patients with depression. Methods In this cross-sectional study, serum cytokines were tested in 40 TA patients and 11 healthy controls using the Bio-Plex Magpix System (Bio-Rad®). The state of depression was measured by the Zung Self-Rating Depression Scale (SDS) in TA patients. Logistic regression analysis was performed to find the risk factors of depression in patients with TA. Results TA patients with depression had higher ESR, hsCRP, NIH, and ITAS.A than patients without depression (16.00 [10.00, 58.50]mm/H vs. 7.50 [4.50, 17.75]mm/H, p = 0.013; 7.60 [2.32, 46.52]mg/L vs. 0.71 [0.32, 4.37]mg/L, p = 0.001; 2.00 [2.00, 3.00] vs. 1.00 [0.00, 2.00], p = 0.007; 7.00 [4.00, 9.50] vs. 1.50 [0.00, 5.75], p = 0.012, respectively). Additionally, the lower age of onset and levels of IL-4, IL-13, eotaxin, and IP-10 were observed in the depressed group compared with the non-depressed (23.50 [19.25, 32.50]pg./ml vs. 37.00 [23.25, 42.50]pg./ml, p = 0.017; 2.80 [2.17, 3.18]pg./ml vs. 3.51 [3.22, 4.66]pg./ml, p < 0.001; 0.66 [0.60, 1.12]pg./ml vs. 1.04 [0.82, 1.25]pg./ml, p = 0.008; 46.48 [37.06, 61.75]pg./ml vs. 69.14 [59.30, 92.80]pg./ml, p = 0.001; 184.50 [138.23, 257.25]pg./ml vs. 322.32 [241.98, 412.60]pg./ml, p = 0.005, respectively). The lower level of IL-4 and age of onset were the independent risk factors for depression in TA patients (OR [95% CI] 0.124 [0.018, 0.827], p = 0.031; 0.870 [0.765, 0.990], p = 0.035, respectively). Conclusion Our data suggested that lower cytokine levels, especially IL-4, might be involved in the development of TA patients with depression. Clinicians can probably use serum IL-4 level testing as a potential indicator of depression in TA.